THE STRUCTURE OF COACH-TEACHER TRAINING IN CANOE POLO WITHIN THE SYSTEM OF CONTINUING EDUCATION IN GREAT BRITAIN (Physical Culture and Sport: Scientific Perspective, 2024)
The article explores the structure of canoe polo coach training within the continuing education system of Great Britain, focusing on its potential implementation in Ukraine's sports education system. Based on the comprehensive analysis of British Canoeing activities and documentation from 2018-2023, the research reveals the organizational framework of the educational process that has proven highly effective in developing qualified coaching professionals. The study demonstrates that successful coach training combines four key components: technical, tactical, physiological, and psychological preparation, integrated through a systematic approach to professional development.The component structure and content of training programs at different qualification levels have been thoroughly examined, revealing a progressive three-tier system of professional development. The research identified specific criteria for assessing coaches' professional competencies at each level, with particular emphasis on practical skills and decision-making abilities. The analysis shows that coaches who complete the full training cycle successfully work with teams at various levels and demonstrate consistent improvement in their athletes' performance.Special attention is paid to the structural elements of educational organization, examining the balance between theoretical and practical training. The study evaluates various assessment methods and the integration of modern teaching technologies, including video analysis, online platforms, and interactive learning tools. The effectiveness of these approaches is supported by data showing significant improvements in coaching outcomes over recent years.The research methodology included document analysis, statistical data evaluation, and comparative analysis of training outcomes. Based on this comprehensive analysis, key success factors have been identified, including the systematic approach to skill development, continuous professional support, and regular competency assessment. The findings have led to specific recommendations for implementing British experience into the structure of canoe polo coach training in Ukraine, taking into account national peculiarities of sport development and the existing sports and pedagogical infrastructure.The practical significance of this research lies in its potential to enhance the quality of coach training in Ukraine through the adaptation of proven international practices while considering local context and resources.
Keywords: canoe polo; coach-instructor; continuing education; structure of professional training; British Canoeing; adaptation of foreign experience; coaching methodology; professional development; sports education system